FREQUENCY OF SIMIAN CREASE IN VARIOUS GENOTYPES OF DOWN SYNDROME (Journal of Medical & Health Sciences Review, 2025)
Background: Down syndrome is the most prevalent chromosomal abnormality worldwide, typically resulting from trisomy 21. While karyotyping remains the gold standard for diagnosis, it is time- consuming and often delayed, especially in resource-limited settings. Objective: To determine the frequency of simian crease among children with Down syndrome and compare its distribution across different genotypes. Methodology: This cross-sectional study was conducted at Children’s Hospital, Faisalabad, from 27th February 2025 to 5th June 2025. A total of 93 children under the age of 18 with genetically confirmed Down syndrome were enrolled using non- probability sampling. Each participant was examined for the presence of simian crease (unilateral or bilateral). Genetic records were obtained from NIBGE to classify genotypes into non-disjunction, translocation, and mosaicism. Results: Out of the 93 participants, 71.0% had a simian crease. Among these, 68.2% were bilateral and 31.8% unilateral. The simian crease was present in 79.5% of children with non-disjunction, 50.0% with translocation, and 25.0% with mosaicism. A significant association was observed between genotype and the presence of simian creases (χ² = 13.32, p = 0.008). No significant association was found with gender (p = 0.071) or age group (p = 0.093). The effect size (Cramér’s V) was calculated to be 0.378, indicating a moderate association. Conclusion: The simian crease is significantly more frequent in children with the non-disjunction form of Down syndrome, suggesting a potential link between genotype and phenotypic expression. While it may aid clinical suspicion, genetic analysis remains essential for definitive diagnosis.